Transformational Leadership And Intellectual Stimulation For Sustainable Santripreneurship: A Case Study Of Islamic Boarding Schools In Lamongan, Indonesia - Muhammad Hafidh Nasrullah (Universitas Islam Darul 'ulum Lamongan, 2026)
Santripreneurship in pesantren is increasingly an important focus in creating students who not only master religious knowledge but also have sustainable entrepreneurial skills. Transformative leadership plays a crucial role in shaping the entrepreneurial spirit of students, by inspiring them to think creatively and innovatively in facing economic and social challenges. In addition, intellectual stimulation through challenging learning and the development of critical thinking skills also strengthens the ability of students to produce new ideas that are relevant to the needs of the times. This study uses a qualitative approach with a case study method at the Lamongan Islamic Boarding School to explore the impact of transformative leadership and intellectual stimulation on the development of santripreneurship. The main findings show that the application of these two elements has succeeded in creating a culture of innovation in Islamic boarding schools and improving students' entrepreneurial skills. The implication of this study is the importance of integrating transformative leadership and intellectual stimulation in the pesantren curriculum to produce independent and adaptive students.